The Reality of Practice of Knowledge Economy Pillars from Jeddah Female Public High Schools’ Leaders in Their Perspective in Their Schools - Al-Mestadi, Soha Hameed; Kareem, Mona Khaled (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the fact of the practice of Female Secondary School Leaders of the pillars of the knowledge economy in the areas of institutional and innovation systems from their perspective. It also aimed to introduce the most prominent challenges that hinder leaders from implementing it in school. It used the interpretative qualitative approach, by conducting interviews with (16) leaders. It concluded that most leaders are not aware of knowledge economy, in addition to the weak supportive school environment for innovation and scientific research and that the school’s role in society is affected by its geographical location. Moreover, there were many impediments that hinder the transition towards knowledge economy, the most important; The centralization of decision-making and slow approval process. The study recommended the establishment of a development unit to promote the culture of the knowledge economy in secondary schools by the Department of Education, in addition to the creation of a procedural guide to help female leaders shift towards knowledge economy.